The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.14742/ajet.6811
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and synchronous participation improve student performance in a blended learning experience

Abstract: Blended learning can create flexibility for students, more efficiently utilise infrastructure, and can provide high-quality learning at scale. We investigated perceived value and learning gains associated with asynchronous eLearning and synchronous face-to-face (f2f) components of a blended learning experience. We hypothesised that individual student preference for eLearning and f2f learning would be variable, but that participation in f2f classes would enhance student learning. Using a design-based research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
(25 reference statements)
3
19
0
Order By: Relevance
“…Blended learning refers to a mixture of instructor-led and technology-based learning that is flexible. Blended learning describes an opportunity that integrates technological innovation and advantages in online learning with the interaction and participation of face-to-face learning benefits (Clark & Post, 2021). The basic concept of blended learning also optimizes oral communication in face-to-face learning with written communication in online learning.…”
Section: Introductionmentioning
confidence: 99%
“…Blended learning refers to a mixture of instructor-led and technology-based learning that is flexible. Blended learning describes an opportunity that integrates technological innovation and advantages in online learning with the interaction and participation of face-to-face learning benefits (Clark & Post, 2021). The basic concept of blended learning also optimizes oral communication in face-to-face learning with written communication in online learning.…”
Section: Introductionmentioning
confidence: 99%
“…These are somewhat contradicting results to the existing literature, which suggested BL and online approaches were not only more effective but also more preferable to traditional face-to-face classrooms (e.g., Bernard et al, 2014;Harmeet Kaur, 2020). However, these findings are somewhat supported by Clark and Post (2021) and Pechenkina et al (2018) who found that BL students preferred to face-to-face components of BL. However, this study using the IET allowed for the probing of specific interactions so it might be that the part of BL and traditional courses that are highly attractive to students are the face-to-face interactions which highlight teacher-student interactions which are often lacking in some BL courses (Lightner & Lightner-Laws, 2016;Smyth et al, 2012).…”
Section: Teacher-student Interactions Supported By Blended Learningmentioning
confidence: 61%
“…Meanwhile, some studies have found positive correlations between synchronous class attendance and student performance (Louis et al, 2016), while other research appears to support the notion that synchronous class attendance does not necessarily lead to higher academic performance (Chapin, 2018;Eisen et al, 2015;Nieuwoudt, 2020). Nieuwoudt (2020) found no significant difference between the final grades of students who attended synchronous classes and students who accessed class recordings, while Clark and Post (2021) concluded that students who independently access well-designed e-learning materials perform just as well as students who attend face-to-face classes. Overall, these findings strongly suggest that it is important to offer flexibility in how students can engage in learning.…”
Section: Student Engagement and Achievement In Hybrid And Online Modelsmentioning
confidence: 97%
“…One way of measuring behavioural engagement is to examine how frequently students participate by accessing key learning experiences (Chung et al, 2022). In hybrid or online learning environments this access can occur through clicks on learning materials in an LMS or attendance at synchronous classes (Clark & Post, 2021). These actions have been recognised as proxies for engagement in hybrid and online learning environments (Dixson, 2015) and are also the focus of this investigation.…”
Section: Student Engagement and Achievement In Hybrid And Online Modelsmentioning
confidence: 99%